Systematic review and meta-analysis of current guidelines, and their evidence base, on risk of renal function after administration of contrast medium for diabetic patients receiving metformin - Qinhui Xu; Weixing Huang; Weixing Huang; Qianyun Li; Tongan Bao; Hua Luo; Xiao Luo (Frontiers in Medicine)
PurposeOur study aimed to determine through a meta-analysis whether continuing metformin use in diabetic patients receiving contrast agents would increase the risk of renal impairment and metabolic abnormalities.MethodsWe searched the PubMed, EBSCO, Medline, and the Cochrane Central Register of Controlled Trials from the inception dates to March 2024. The included studies comparing metformin users and non-users during contrast agent administration in diabetic patients. Outcome measures included contrast-induced acute kidney injury (CI-AKI), serum creatinine, estimated glomerular filtration rate (eGFR), lactate level, and incidence of metabolic acidosis. We used odds ratio (OR) for dichotomous outcomes and weighted or standardized mean difference (WMD or SMD) for continuous outcomes, depending on scale consistency across studies.ResultsAnalysis involved 2 randomized controlled trials and 5 retrospective cohorts comprising 2020 patients. There were no significant differences between the metformin and non-metformin groups in CI-AKI incidence (OR: 0.87, 95% CI: 0.63–1.20), changes in renal function (serum creatinine: SMD: −0.15, 95% CI: −0.64–0.35; eGFR: WMD: 3.35, 95% CI: −1.60–8.29), incidence of metabolic acidosis (OR: 0.90, 95% CI: 0.57–1.43), and lactate levels (SMD: 0.29, 95% CI: −0.53–1.11). Sensitivity analysis excluding one study revealed a significant reduction in creatinine with metformin. Logistic regression meta-analysis showed that metformin use was not significantly associated with CI-AKI or metabolic acidosis, while contrast volume was the only consistent predictor of CI-AKI. Lower baseline CO2 was independently associated with increased risk of metabolic acidosis.ConclusionsOur analysis indicates that continuing metformin during contrast agent administration does not increase the risk of CI-AKI, acidosis, or eGFR compared to discontinuation or non-use of metformin. Additionally, continuation of metformin may be associated with a modest reduction in serum creatinine levels after contrast exposure. However, the limited quality of included studies may weaken the strength of these conclusions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023459602, identifier: CRD42023459602.